The infection pressure of potato leafroll virus and potato virus Y in relation to aphid populations in Cyprus - Ioannou, Nicolas (My University, 1989)
The infection pressure of two viruses, potato leafroll (PLRV) and potato virus Y (PVY), both common in seed potatoes grown in Cyprus, was determined in three experiments in 1982-83. Virus-free bait plants, of potato and four other species, were exposed weekly to field infection during the growing season (March-June), and then returned to an aphid-free glasshouse for symptom expression. Only tobacco plants produced clear symptoms enabling reliable assessment of PVY infection pressure. When assessed with ELISA or by tuber indexing, the potato plants were efficient baits for both viruses whose infection period commenced at emergence (mid March to early April) and ended within 6-7 weeks. The seasonal trend of aphid populations, determined with Moericke traps or 100-leaf counts, correspond to that of virus spread. Correlation and regression analysis of aphid and virus data implicated the alate form of Myzus persicae as the principal vector of both viruses.
Keywords: Bait plants; Moericke trap; Myzus persicae; Seed potatoes; Virus vectors